2015
DOI: 10.1007/82_2015_483
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity Variants and RNA Quasispecies

Abstract: By now, it is well established that the error rate of the RNA-dependent RNA polymerase (RdRp) that replicates RNA virus genomes is a primary driver of the mutation frequencies observed in RNA virus populations-the basis for the RNA quasispecies. Over the last 10 years, a considerable amount of work has uncovered the molecular determinants of replication fidelity in this enzyme. The isolation of high- and low-fidelity variants for several RNA viruses, in an expanding number of viral families, provides evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 98 publications
(130 reference statements)
1
60
0
Order By: Relevance
“…Our lab has constructed a series of FMDV attenuated strains using other route and we found that the trend of virus attenuation in the sucking mice model and natural host is identical although the degree of attenuation quantity is different (unpublished data, inpreparation), which showed that attenuation of FMDV in the sucking mice model does imply attenuation in natural hosts. Besides, fidelity-altering mutations associated with single or few residues, combining these with other conventional and effective attenuating mutations or methods may be a good strategy to further reduce reversion to virulence as live attenuated vaccines (LAVs) (Borderia et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Our lab has constructed a series of FMDV attenuated strains using other route and we found that the trend of virus attenuation in the sucking mice model and natural host is identical although the degree of attenuation quantity is different (unpublished data, inpreparation), which showed that attenuation of FMDV in the sucking mice model does imply attenuation in natural hosts. Besides, fidelity-altering mutations associated with single or few residues, combining these with other conventional and effective attenuating mutations or methods may be a good strategy to further reduce reversion to virulence as live attenuated vaccines (LAVs) (Borderia et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…These and other studies have established the important concept that to maintain an adequate fitness and a good survival probability, a virus population must keep its genome heterogeneity within a suitable range: too low a diversity impairs adaptability, and too high a diversity may approach the population to an extinction threshold Zeng et al, 2014). Several studies have demonstrated an attenuation phenotype associated with low-or high-fidelity viral mutants (Borderia et al, 2016). In a clinical setting, maintaining mutant spectra of viruses within an optimal range is one of the predictors of viral survival and progression toward disease (Section 8.8 in Chapter 8).…”
Section: Virus Resistance To Mutagenic Agents: Multiple Mechanisms Anmentioning
confidence: 98%
“…These high mutation rates are a major driver of RNA virus evolution, and the rapid emergence of adaptive mutations that affect tropism, virulence, fitness and drug resistance. Ex-patriate Canadian Dr. Marco Vignuzzi from the Pasteur Institute presented his approach to combine experimental evolution with mathematical modeling to determine the evolutionary trajectory of RNA virus mutants [15,16]. Deep sequencing data, combined with bioinformatics, permitted representation of mutations in 2D space, while fitness is represented in the third dimension.…”
Section: Monitoring and Visualizing Rna Virus Evolutionmentioning
confidence: 99%